Baf53a is involved in survival of mouse ES cells, which can be compensated by Baf53b. Issue 1 (December 2017) - Zhu, Bo; Ueda, Atsushi; Song, Xiaohong; Horike, Shin-ichi; Yokota, Takashi; Akagi, Tadayuki
Abstract The human Baf (Brg1/Brm associated factor) complex, also known as the mammalian SWI/SNF chromatin-remodeling complex, is involved in a variety of cellular processes. The pluripotency and self-renewal abilities are major characteristics of embryonic stem (ES) cells and are regulated by the ES cell-specific BAF (esBAF) complex. Baf53a is one of the subunits of the esBAF complex. Here, we found that Baf53a was expressed in undifferentiated ES cells and that it interacted with Oct3/4. Analyses of tetracycline-inducible Baf53a conditional knockout ES cells revealed that the undifferentiated markers, including Nanog and Oct3/4, were expressed in Baf53a-deficient ES cells; however, growth of the cells was repressed, and expression of p53, p21, and cleaved Caspase 3 was increased. Cell death of Baf53a-deficient ES cells was rescued by overexpression of Baf53a, but not by the Baf53a M3 mutant (E388A/R389A/R390A). Interestingly, Baf53b, a homologue of Baf53a, rescued cell death of Baf53a-deficient ES cells. Baf53a-deficient ES cells overexpressing exogenous Baf53a or Baf53b remained in the undifferentiated state, proliferated, and repressed expression of p21. In summary, our findings suggest that Baf53a is involved in the survival of ES cells by regulating p53 and Caspase3, and that Baf53b is able to compensate for this functional aspect of Baf53a.